2016
DOI: 10.1037/neu0000253
|View full text |Cite
|
Sign up to set email alerts
|

Environment and cognitive aging: A cross-sectional study of place of residence and cognitive performance in the Irish longitudinal study on aging.

Abstract: Our findings suggest higher cognitive functioning for urban residents, although childhood residence modulates this association. Suggestions for further developments of these results are discussed. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 112 publications
(179 reference statements)
2
39
1
Order By: Relevance
“…These results correspond to some of the evidence in the literature (Cassarino et al, 2016, Nunes et al, 2010, Russ et al, 2012) as well as our previous analysis which showed higher odds of cognitive impairment in areas with low levels of land use mix (Wu et al, 2015b). However, a high REAT score, which indicates poor quality of micro-scale environment, was associated with lower odds of cognitive impairment and dementia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results correspond to some of the evidence in the literature (Cassarino et al, 2016, Nunes et al, 2010, Russ et al, 2012) as well as our previous analysis which showed higher odds of cognitive impairment in areas with low levels of land use mix (Wu et al, 2015b). However, a high REAT score, which indicates poor quality of micro-scale environment, was associated with lower odds of cognitive impairment and dementia.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence from epidemiological research supports the presence of urban/rural differences in dementia prevalence and cognitive function (Cassarino et al, 2016, Nunes et al, 2010, Russ et al, 2012). Area deprivation and some physical and social environmental factors such as features of land use, access to local services and resources, have also been related to cognitive function in older people (Clarke et al, 2012; Lang et al, 2008; Watts et al, 2015; Wu et al, 2015a, Wu et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these results, Chapman and Underwood (1998) reported shorter fixations for drivers in urban rather than rural environments, suggesting more exploratory scanning strategies for complex environments. In our recent work (Cassarino et al, 2016), we showed that urban healthy older people had better executive functions than people living in rural areas after controlling for socio-economic, health, and lifestyle confounders, further indicating that different environments could be associated with distinct perceptual and cognitive abilities. Although the study did not manipulate environmental complexity directly, the results suggest a direct association between living in a complex environment and cognitive functioning in older age.…”
Section: Complexity and Cognitive Performancementioning
confidence: 68%
“…The plausibility of a direct environmental impact on cognition has been supported by animal studies (Engineer et al, 2004; Herring et al, 2009; Hannan, 2014), as well as recent epidemiological evidence on geographical variations of cognitive functioning in aging when socio-economic and lifestyle factors were controlled for (Wu et al, 2015; Cassarino et al, 2016). Experimental evidence on environmental restorativeness for cognitive skills, i.e., the potential for natural, green environments to restore depleted attentional capacities as described within attention restoration theory (Kaplan and Kaplan, 1982; Kaplan, 1995; Hartig et al, 2003; Berman et al, 2008), also suggests a direct link between environment and cognition in older adults (Gamble et al, 2014).…”
Section: Environmental Measures Linking Complexity To Cognitive Agingmentioning
confidence: 93%
“…Recently researchers have approached to examine not only influence of factors such as gender, age or level of education, but also have aimed to include the effect of neighborhood environment and lifestyle on cognitive functioning and decline of cognitive functions, or well-being and health in later life in the picture (Besser, McDonald, Song, Kukull, & Rodriguez, 2017;Cassarino, O'Sullivan, Kenny, & Setti, 2016; Weuve, Barnes, Evans, & Mendes de Leon, 2015;Eibich, Krekel, Demuth, & Wagner, 2016;Lee & Waite, 2017;Saenz, Downer, Garcia, & Wong, 2017;Watts, Ferdous, Diaz Moore, & Burns, 2015;Wörn, Ellwardt, Aartsen, & Huisman, 2017;Wu et al, 2017). Schooler (1984) presented a theory of environmental influences on cognitive functions, which may be applied in the case of busy nature of urban areas that makes city residents learn quicker pace in solving tasks.…”
Section: Introductionmentioning
confidence: 99%